Rethinking humanitarian intervention in the 21st century - Warren, Aiden; Grenfell, Damian (Edinburgh University Press, 2017)
Since the end of the Cold War, humanitarian interventions have continued to evolve and respond to a wide range of political crises. These insightful essays focus on the challenges associated with interventions when facing conflict and human rights violations, unmitigated systematic violence, state re-building, human mobility and dislocation. Each chapter is linked to the rest through three defining themes that permeate the book: the evolution of humanitarian interventions in a global era; the limits of sovereignty and the ethics of interventions; and the politics of post-intervention: (re)-building and humanitarian engagement. The authors incorporate a variety of case studies including Kosovo, Timor-Leste, Syria, Libya and Iraq, and examine the complexity of interventions across their different dimensions, including relevant doctrines such as R2P, ́⁰Use of Forcé⁰₉ and Human Security.